О методике проведения натурных обследований гидротехнических сооружений на искусственных водных объектах Беларуси - Levkevich Виктор; Malashevich Валерий; Lasuta Геннадий (Vestnik of the Institute for Command Engineers of the MES of the Republic of Belarus, 2013)
Concept of the methodology for carrying-out full-scale surveys of the waterworks on artificial water bodies of Belarus is presented.